‘We have the solutions to our own problems’: supporting civil society in Nigeria - Overseas Development Institute (ODI, 2014)
Development assistance programmes that start from careful analysis of what works and what does not in country contexts are still remarkably rare. One reason for this is the lack of well documented examples of ‘politically’ smart aid programming. To this end, this film outlines the experience of the State Accountability and Voice Initiative (SAVI), a DFID-funded programme in Nigeria providing support to civil society, media and governmental organisations.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Twenty years of UK governance programmes in Nigeria - Piron, Laure-Hélène; Cummings, Clare; Williams, Gareth; Derbyshire, Helen; Hadley, Sierd (ODI, 2021)
This Flagship report analyses 20 years of governance programmes in Nigeria funded by the UK Department for International Development (DFID) and the Foreign, Commonwealth and Development Office (FCDO) in the North-western states of Jigawa (since 2001), Kano (since 2005) and Kaduna (since 2006), as well as the North-eastern state of Yobe (since 2011). The report’s main research question is whether, how, under what conditions and for whom UK-funded state-level governance programmes in Nigeria have contributed to sustained changes in governance, and related changes in health and education. ... The report concludes with the following recommendations: To international development partners: 1. Invest for the long term – 10 to 20 years – combining support for both state and nonstate actors. 2. Ensure programmes have the strategic-level mandate, managerial capacity and frontline staff skills to pursue politically savvy opportunities. 3. Take PEA to the next level by unpacking causal mechanisms, understanding incentives and designing interventions to make change happen. 4. Give governance programmes the ability to flex between core governance and service delivery issues. 5. Incentivise greater collaboration between governance and sector programmes. 6. Incentivise greater attention to gender, and to social inclusion beyond disability issues, in governance programming. To FCDO: 7. Empower and resource FCDO teams to enable TWP programmes, ensuring decision-making by country teams to respond to local priorities. 8. Re-imagine TWP for FCDO Nigeria, giving implementers the space to operate in TWP ways. 9. Incentivise stronger collaboration between PERL, Lafiya (health programme) and the Partnership for Learning for All in Nigerian Education. 10. Invest in impact data analysis. To partner governments in Nigeria and beyond: 11. Explicitly set out the objectives for which you would like to receive assistance. 12. Use TWP principles to decide how development partners can support your political objectives and the scope for politically-feasible and mutually-beneficial collaboration. 13. Invest in the coordination of development partners. To non-state partners in Nigeria and beyond: 14. Join coalitions to achieve your priorities. 15. Select development partners which can strengthen your skills, not just fund your activities.

Thinking and Working Politically: Lessons from FOSTER in Nigeria - Lopez Lucia, Elisa; Buckley, Joanna; Marquette, Heather; McCulloch, Neil (Research Paper, 2017)
The Facility for Oil Sector Transparency and Reform (FOSTER) was a £14 million programme that has helped Nigeria to transform its governance of the oil and gas industry. FOSTER ran from 2011 to mid-2016, and used an explicit ‘thinking and working politically’ (TWP) approach. It was funded by the UK Department for International Development (DFID) and managed by Oxford Policy Management (OPM). This paper seeks to identify the factors that drove – or constrained – FOSTER’s achievements, and asks what this can tell us about TWP, particularly in challenging political and sectoral contexts. FOSTER sought to help strengthen oversight and accountability in Nigeria’s oil sector. It aimed to support reformers within government institutions that ‘supply’ accountability (those governing how oil and gas revenues are collected and managed), and to support civil society organisations, parliament, the media and the Nigeria Extractive Industries Transparency Initiative to ‘demand’ reform. In addition, FOSTER commissioned a series of studies and provided media training to help broaden understanding of the sector and highlight the need for reform. This paper examines the outcomes from five ‘clusters’ of FOSTER interventions. The FOSTER team viewed the first three of these in the list below as successful, whereas the latter two did not deliver on expectations but offer important opportunities for learning: • Support to the Nigerian Extractive Industries Transparency Initiative • Support to demand-side actors to promote transparency and accountability in the oil sector • Support for the passage of the Petroleum Industry Bill • An oil spill-mapping social media project • Support to the Department of Petroleum Resources The analysis drew on 44 semi-structured interviews conducted during a month of fieldwork in Abuja and Lagos; on reviews of the programme’s monitoring, evaluation and learning frameworks; and on newspaper articles and grey literature on Nigeria’s oil sector.2

The SAVI programme in Nigeria: Towards politically smart, locally led devlopment - Booth, David; Chambers, Victoria (ODI, 2014)
 More examples are needed of aid programming that works by being responsive to country realities: politically smart, problem-driven and locally led  DFID’s SAVI programme has revealed a hitherto untapped potential for change leading to better development results at state level in Nigeria  SAVI provides low-profile support to state-level organisations and partnerships, building their capacity to engage constructively with government  It avoid the pitfalls of a donor-driven approach by ‘taking the money off the table’  This illustrates the power of facilitated multi-stakeholder engagement and the disadvantages of seeing this in terms of ‘supply side’ and ‘demand side’ governance  The set-up of the DFID suite of state-level programmes, with separately managed sector support and ‘governance’ initiatives, has limited realisation of the potential  Key enabling conditions were that DFID provided space for an experience-based design process and permitted tangible results to be judged retrospectively, not pre-programmed

Strengthening Advocacy and Civic Engagemetn in Nigeria - Chemonics (Chemonics International, 2018)

State Accountability and Voice Initiative (SAVI) - Approach Paper Series - SAVI (DFID, 2016)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact. Our approach is summarized in the Introduction to SAVI’s way of working. We have broken our approach down into key components – depicted in the form of our ‘knowledge tree’ –...
Keywords: IMPORTANT

SAVI Approach Paper 9: Engaging State Houses of Assembly - SAVI (DFID, 2015)
The overall aim of SAVI engagement with SHoAs is to promote lasting reforms that are not dependent on external funding and which promote an increasingly more responsive and accountable relationship between Nigerian state governments and their citizens. SHoAs are supported to be more effective agents of citizen voice and public accountability, demanding better performance from...

SAVI Approach Paper 8: Engaging the Media - SAVI (DFID, 2015)
The overall aim of SAVI engagement with the media is for media representation of citizens’ interests to become normal, and play its part in helping state governments to be more responsive, inclusive and accountable to their citizens. Media partners – individual media personnel and selected media houses – are supported to be more effective agents...

SAVI Approach Paper 7: Promoting Gender Equality and Social Inclusion - SAVI (DFID, 2015)
We promote attention to gender equality and social inclusion in all of our engagement with CS groups, the media and SHoAs, and in all of the issues and processes they work on. In all the states we work in, we also support partners to focus on some issues and form some partnerships and networks which...

SAVI Approach Paper 6: Engaging Civil Society - SAVI (DFID, 2015)
SAVI state teams provide support to CS groups to become more effective agents of citizens’ voice and public accountability, through a variety of mutually reinforcing interventions. These include: hands-on support to demonstration civil society Advocacy Partnerships (APs) facilitating working partnerships between civil society APs, SHoAs, and the media brokering working relationships between all of these...

SAVI Approach Paper 5: Defining and Measuring Results - SAVI (DFID, 2015)
SAVI aims to facilitate replicable and sustainable processes of citizen engagement in governance. The programme in each state is locally defined, flexible and adaptive, and results are not predictable in advance. Standardised monitoring tools are not applicable, and consequently we have evolved our tools and frameworks during the programme through processes of learning by doing....

SAVI Approach Paper 4: Thinking and Working Politically - Supporting partners and staff through a participatory apporach to political economy analysis - SAVI (DFID, 2015)
Thinking and acting politically is central to the SAVI programme. We support staff and partners to analyse the power relations that shape change in their state, and to use this knowledge to inform their decision-making. This includes decisions made by SAVI state teams relating to the issues and partners they engage with and support, and...

SAVI Approach Paper 3: Theory of Change - SAVI (DFID, 2015)
SAVI’s theory of change is a simple, practical guide that staff and partners use to plan and to monitor change – as well as to reflect on and enhance their own effectiveness. It sets out broad stages of attitude and behaviour change over time to facilitate effective citizen engagement in governance processes, systems and structures....

SAVI Approach Paper 2: Programme Design - SAVI (DFID, 2015)
SAVI supports citizen engagement in governance through a facilitated partnership approach, in contrast to the usual approach of grants to civil society organisations (CSOs). The overall aim is to facilitate and support working relationships and processes of reform that are home-grown, self-sustaining and, after initial engagement, not dependent on external support. Our way of working...

SAVI Approach Paper 15: Introduction to PERL: the SAVI Successor Programme - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

SAVI Approach Paper 14: Learning, Adaptation and Communications - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme, aiming to put learning and adaptation at the centre of all decision-making. Learning and adaptation takes place in SAVI at three levels: the work of partners; the work of SAVI delivery teams; and the enabling environment of the programme as a whole. Achieving...

SAVI Approach Paper 13: Measuring Value for Money and using Value for Money Analysis - SAVI (DFID, 2016)
SAVI has established its own framework for assessing Value for Money in annual performance – in relation to expenditure, economy, efficiency, effectiveness and equity. Routine tracking and analysis of expenditure and economy ensure that inputs are supplied and services delivered to partners in line with SAVI’s core values, whilst also meeting DFID requirements and competing...

SAVI Approach Paper 12: Managing Programme Finances to Support Adaptive, Locally-led Processes of Citizen Engagement in Governance - SAVI (DFID, 2016)
SAVI, is seeking to support processes of citizen engagement in governance in ways that are effective in influencing reform, and that are able to take on a life of their own without continuing donor support. SAVI is also an adaptive programme, putting learning and adaptation at the centre of all decision-making. Money is used and...

SAVI Approach Paper 11: Managing and Staffing an Adaptive Citizen Engagement Programme - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme putting learning and adaptation at the centre of all decision-making. In relation to management and staffing SAVI has established the following approaches to facilitate this: – An adaptive approach to programme management: Full time strategic technical leadership, that works closely with and complements...

SAVI Approach Paper 10: Engaging State Governments - SAVI (DFID, 2015)
SAVI as a programme does not directly work with state governments – but we work in close conjunction with sister programmes who are supporting state governments on governance and sector reforms. SAVI supports non-government and SHoA partners to play their part in promoting more responsive, inclusive and accountable state governance delivering better services for citizens....

SAVI Approach Paper 1: Core Values - SAVI (London, 2015)
Governance reform is about government and citizens working together in more responsive, inclusive and accountable ways for the benefit of citizens. More responsive, inclusive and accountable attitudes and behaviour on the part of government and non-government stakeholders are the critical factors which lead to meaningful reform processes, and replicate and sustain reforms beyond the lifetime...

Politically smart support to economic development: DFID experiences - Booth, David (ODI, 2016)

PDIA in action - Andrews, Matt; Samji, Salimah (Center for International Development, Harvard University, 2021)
Learning from our experience in 2020, we asked the alumni of our HKS Implementing Public Policy (IPP) Executive Education program, if they wanted to work with our students on their nominated problems. Eight IPP alumni, William Keith Young, Adaeze Oreh, Milzy Carrasco, Kevin Schilling, Artem Shaipov, George Imbenzi, David Wuyep, and Raphael Kenigsberg, who had been trained on PDIA and implementation, signed up to work with our students. Thirty-seven students signed up to take the course beginning January 26th, 2021. The students worked across eight teams and adopted a problem driven approach to foster learning that could help their authorizers develop an action learning strategy to their nominated challenge. This book highlights the students’ work drawing from their blogs as well as the event series. There are 8 sections, one for each of the teams and the problems they worked on during the course. We hope you enjoy reading their stories! Scan the QR Code at the end of each section to learn more.

Nigeria Public Sector Accountability and Governance Programme - Business Case - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Introduction to SAVI's way of working - State Accountability and Voice Initiative (SAVI) - SAVI (DFID, 2015)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact.  SAVI Approach Papers summarise key aspects of SAVI’s way of working. They explain what we do, and why – and link to relevant tools and frameworks. Our approach is summarized in...
Keywords: Practice

Insights for Influence: Understanding Impact Pathways in Crisis Response - Clark, Louise; Carpenter, Jo; Taylor, Joe (Institute of Development Studies, 2023)
The Covid-19 Responses for Equity (CORE) programme was a three-year initiative funded by the Canadian International Development Research Centre (IDRC) that brought together 20 projects from across the global South to understand the socioeconomic impacts of the Covid-19 pandemic, improve existing responses, and generate better policy options for recovery. The research covered 42 countries across Africa, Asia, Latin America, and the Middle East to understand the ways in which the pandemic affected the most vulnerable people and regions, and deepened existing vulnerabilities. Research projects covered a broad range of themes, including macroeconomic policies for support and recovery; supporting essential economic activity and protecting informal businesses, small producers, and women workers; and promoting democratic governance to strengthen accountability, social inclusion, and civil engagement. The Institute of Development Studies (IDS) provided knowledge translation (KT) support to CORE research partners to maximise the learning generated across the research portfolio and deepen engagement with governments, civil society, and the scientific community. As part of this support, the IDS KT team worked with CORE project teams to reconstruct and reflect on their impact pathways to facilitate South-South knowledge exchange on effective strategies for research impact, and share learning on how the CORE cohort has influenced policy and delivered change. This report presents an overview of these impact pathways and the lessons learnt from a selection of the projects chosen to represent the diversity of approaches to engage policymakers, civil society, and the media to generate and share evidence of the effect of the pandemic on diverse vulnerable groups.

Implementing Adaptive Approaches in Real World Scenarios: A Nigeria Case Study, with Lessons for Theory and Practice - Bridges, Kate; Woolcock, Michael (The World Bank, 2019)
How does adaptive implementation work in practice? Drawing on extensive interviews and observations, this paper contrasts the ways in which an adaptive component of a major health care project was implemented in three program and three matched comparison states in Nigeria. The paper examines the bases on which claims and counterclaims about the effectiveness of these approaches were made by different actors, concluding that resolution requires any such claims to be grounded in a fit-for-purpose theory of change and evaluation strategy. The principles of adaptive development may be gaining broad acceptance, but a complex array of skills, expectations, political support, empirical measures, and administrative structures needs to be deftly integrated if demonstrably positive operational results are to be obtained, especially when undertaken within institutional systems, administrative logics, and political imperatives that are predisposed to serve rather different purposes.

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (Working Paper 525, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

Enabling citizen-driven improvement of public services. Leveraging Technology to Strengthen Accountability in Nigerian Healthcare - ICT4SA (World Bank and Reboot, 2015)
Effective public service delivery begins with knowing whether the services offered are working as intended. We launched a system to enable citizen input on the delivery of public services.

Adaptive programming in practice: shared lessons from the DFID-funded LASER and SAVI programmes - Derbyshire, Helen; Donovan, Elbereth (Synthesis Paper 3, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others).
Keywords: IMPORTANT; Practice

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery